PENGUNGKAPAN TRANSPARANSI LAPORAN KEUANGAN PARTAI POLITIK SEBAGAI DASAR GOOD POLITICAL PARTY GOVERNANCE (Study Kasus Pada Partai Amanat Nasional Kabupaten Asahan) - Sapriani Sapriani; Nurlaila Nurlaila; Nurul Inayah (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to determine the disclosure of accountability for party finances towards a good political party governance. The problem studied in this study is the finances of political parties which are required to make fundamental improvements, namely to build institutional transparency and accountability in order to regain the trust of the public. Political parties are required to develop the values of transparent and responsible political ethics. The object of this research is the Asahan Regency National Mandate Party. This research is a qualitative research with a descriptive approach that focuses on the understanding of informants and the views of researchers. The research data is sourced from primary data obtained by in-depth interviews with informants who are considered competent in their fields. The data used are subjects derived from interviews and documentary data. Data collection methods used were interviews and documentation studies. The results of the research show that the accountability and financial transparency of the National Mandate Party can be said to be good, but there must be improvement. This is evidenced by the fact that the use of aid funds is relatively closed to the public and the accountability for assistance received from membership dues, third party donors and DPR infaq is not made clear financial reports. So it cannot be said that the National Mandate Party has described good political party governance.